BOS Fund Allocation Policy (A Site Study at State Elementary School of Kedung Pucang Purworejo) - Murnihati, Tri; , Prof. Dr. Bambang Sumardjoko; , Dr. Phil. Dewi Candraningrum, M.Ed (2013)
The objectives of this study were to describe (1) characteristic of BOS fund allocation planning at State Elementary School of Kedung Pucang Purworejo; (2) characteristic of the use of BOS fund at State Elementary School of Kedung Pucang Purworejo; and (3) characteristic of the accountability of the use of BOS fund at State Elementary School of Kedung Pucang Purworejo. It was a qualitative research using ethnography design. The main subjects included the principal, BOS treasurer, and teachers. Data collection methods used interview, observation, and documentation. Data analysis was started from data collection, then (2) data reduction, (3) data display, and (4) drawing conclusion. Checking of data validity used credibility, transferability, confirmability, and dependability. The findings suggested that (1) the allocation of School Operational Assistance (BOS) fund planning in State Elementary School of Kedung Pucang Purworejo was conducted in a democratic and transparent manner. Principal formed a management team for School Operational Assistance (BOS) and conducted need analysis with the principle of priority and recorded students who received the fund together. The allocation plan was contained in the school proposed document where the need of learning was allocated by 70%. This percentage was greater than honorary that was only 20%. (2) Use of the fund in SDN Kedung Pucang was done on a quarterly basis by planning it first. The amount of School Operational Assistance (BOS) fund to be used by State Elementary School of Kedung Pucang was Rp. 27,840,000.00. It would be spent on goods and services, including the operational needs of schools as learning needs of students. Beyond the operational needs of the school were not allowed to use the fund. Use of the fund was by concerning the quality, availability, and affordability of goods / services of the school operational needs. (3) Accountability of the use of School Operational Assistance (BOS) fund was done by the preparation of financial accountability report. The content of the report included a document of the realization of the use of fund, letter of accountability, School Operational Assistance (BOS) fund accounting, and also evidence of expenditure such as receipts signed by the principal. The report would be sent to BOS management team in Purworejo on a quarterly basis. In addition to being accounted to District management team, it was also accounted to school citizens through hanging the accountability report on the bulletin board, installation of banners, as well as dissemination of the use of the fund.